If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 24 = 5x + 32 Reorder the terms: 24 + 3x = 5x + 32 Reorder the terms: 24 + 3x = 32 + 5x Solving 24 + 3x = 32 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 24 + 3x + -5x = 32 + 5x + -5x Combine like terms: 3x + -5x = -2x 24 + -2x = 32 + 5x + -5x Combine like terms: 5x + -5x = 0 24 + -2x = 32 + 0 24 + -2x = 32 Add '-24' to each side of the equation. 24 + -24 + -2x = 32 + -24 Combine like terms: 24 + -24 = 0 0 + -2x = 32 + -24 -2x = 32 + -24 Combine like terms: 32 + -24 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| 19-5x=-7x+11 | | y=2(-3+4) | | 9n-9=0 | | 9+4p=1 | | 20=3(5y-4) | | 1+6n=5n-5 | | 7(c-3)=6(4+c) | | 4x+8.2=2(3x-3.9) | | b+(b+25000)=575000000 | | 5(x+1.21)=4x | | 8(w-9)-(3w-7)=4w | | 4x+8.2=(3x-3.9) | | -32+4v=-5(3v-2) | | 8u^2+u-9=0 | | 15(y+2)=45 | | 0.4x+0.8=-1.6 | | 4x^2-8x-14=0 | | x+7+4x+3=180 | | 12r-2=-98 | | 16=4k-9 | | x^3-11x^2= | | 4(n-6)-(9+2n)=n | | 17=-2p-3 | | 68=-4(5+3) | | -17+8=42 | | -2c+-5c=-29 | | -18-90=18 | | -6r+8=8 | | 2x-11-5=6 | | 24-3a=12 | | -6x+10=15-7x-5 | | 120=8x+7x |